TEACHERS’ PERSPECTIVES ON THE IMPLEMENTATION OF TECHNOLOGY IN TEACHING ENGLISH FOR YOUNG LEARNERS (JOSAR (Journal of Students Academic Research), 2025)
The aim of this paper is to find out the teachers’ perspective on the implementation of technology in teaching English for young learners. Qualitative was applied in this research. The instruments used were observation and interview. Observation was used to find out what kinds of technology were implemented in the classroom by teachers. The interview was done to find out in-depth what their perceptions on the use of technology in their teaching learning process are. The findings showed that the technology was used by the teachers were laptops, LCD, speakers, Power Point, Canva, Youtube, Baamboozel and Wordwall. Besides, the implementation of technology for learning has a positive view from the teachers’ point of view, namely, improving the quality of the learning process, attracting students' interest, helping teachers in the teaching process, creating an interactive, active and fun learning environment, and improving student motivation. From the result findings it can be concluded that teacher get advantages in embedding technology on teaching English for young Learners. It is suggested to teachers to intergrate technology in their classroom to engage the students.